The “fotoscop” by Joaquim Gomis and Joan Prats. Sequence, order, and cadence - González Gracia, Daniel; Acilu Fernández, Aitor (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
After years of friendship and collaboration in the cultural circles that defended the new art in Barcelona in the 1930s, Joaquim Gomis and Joan Prats met again after the war to conceive a unique photographic artifact that they would call “fotoscop”. During the following two decades, both would portray through their particular visual language and through their most diverse formats motifs as disparate as the anonymous rural constructions of the island of Ibiza or the chimerical architectures of Antoni Gaudí, casting an unusual gaze on both scenarios. But what exactly did that photographic device consist of? What were its visual characteristics and conceptual properties? How was the process of gestation of its photographic language? And what impact did this artifact have on the field of architectural criticism during the 1950s and 1960s regarding the critical judgment of Gaudí and Ibizan architecture? This article will delve into these questions based on a critical review of the testimonies and materials bequeathed by its protagonists, some of them unpublished, in order to establish new links and comparisons with previous contributions by other authors, with the aim of highlighting the value of this legacy.
Keywords: Photography; Joaquim Gomis; Joan Prats; Fotoscop; Antoni Gaudí; Ibiza